(untitled) (Revista Española de Fisiología, 1992)
The present work analyzes the role of food and water intake, nitrogen balance, and in vivo D-glucose intestinal absorption in body weight gain during the second half of pregnancy in malnourished mother rats. Our results indicate that nitrogen balance and intestinal absorption of D-glucose were not changed as a result of food restriction, but important negative correlations between water intake and micturition and weight gain and micturition were found in experimental mothers. The retention of water seems to be one of the most important factor influencing body weight gain in malnourished mother rats in the second half of pregnancy.